Self-Responsibility and Activation for Lone Mothers in the United Kingdom. (January 2019) - Millar, Jane
Lone mothers make up a quarter of all families with children in the United Kingdom and have been one of the key target groups for activation policies for the past two decades. In a relatively short period of time, the U.K. system has changed from treating lone mothers as carers to treating them as workers. Most lone mothers are now required to seek work, or to be in work, in order to be eligible for state support. These developments place self-responsibility at the center of welfare reform and paid work as the core of self-responsibility. The focus is very much on the individuals and their labor market obligations and downplays their social obligations, for example, to care for their children or other family members. The capacity to make choices about when and how much to engage in paid work is much reduced. This article explores what these developments have meant for lone mothers in the United Kingdom. The first main section outlines the key policy approaches and measures, highlighting the underpinning concepts of self-responsibility. The discussion also explores the experiences of lone mothers in relation to these policies, drawing on data from a long-term qualitative study. The second main section focuses on a new policy development—the introduction of Universal Credit—in which promoting an employment-based self-responsibility is unequivocally central to the policy aims and design.